(untitled) (Research, Society and Development, 2022)
Objective: to report the experience of developing a nursing protocol for the care of the deaf community in the face of spontaneous demand in primary care. Methods: this is an experience report focused on the elaboration of a protocol that will contribute to the deaf community and should be used by professionals in the nursing area, in spontaneous demand care in Primary Care. It took place in Fortaleza-CE in the period April - May 2022. Results: the research phases and their results are described in the steps: invitation to specialist professionals, creation of the development group, meetings for debates and discussions, elaboration and construction of the protocol by flowchart, facilitating professional consultation. Conclusion: the protocol aims to improve these services and the access of the deaf patient in the health system, offering an opportunity for a more accessible communication in LIBRAS. In addition, strategies were developed to improve the practice of care provided by these professionals to patients, with a view to adopting this method in other Brazilian municipalities with possible adaptations.